Patterns of avian haemosporidian infections vary with time, but not habitat, in a fragmented Neotropical landscape - Rivero-de Aguilar, Juan (2018)
Habitat loss has the potential to alter vertebrate host populations and their interactions with parasites. Theory predicts a decrease in parasite diversity due to the loss of hosts in such contexts. However, habitat loss could also increase parasite infections as a result of the arrival of new parasites or by decreasing host immune defenses. We investigated the effect of habitat loss and other habitat characteristics on avian haemosporidian infections in a community of birds within a fragmented landscape in northwest Ecuador. We estimated Plasmodium and Haemoproteus parasite infections in 504 individual birds belonging to 8 families and 18 species. We found differences in infection status among bird species, but no relationship between forest fragment characteristics and infection status was observed. We also found a temporal effect, with birds at the end of the five-month study (which ran from the end of the rainy season thru the dry season), being less infected by Plasmodium parasites than individuals sampled at the beginning. Moreover, we found a positive relationship between forest area and Culicoides abundance. Taken as a whole, these findings indicate little effect of fragment characteristics per se on infection, although additional sampling or higher infection rates would have offered more power to detect potential relationships. © 2018 Rivero de Aguilar et al.This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.